Harmonized system of quality assessment for electronic components. Semiconductor devices. Optoelectronic devices. Blank detail specification for avalanche photodiodes (APDs) with/without pigtail, for fibre optic systems or subsystems. (15th August 1997) - British Standards Institution,
No abstract available